Spatial distribution of soil water erosion at Al-Hawiz Dam in Western Syria using CORINE model - Al-Rubaye, Aymen A.; Barakat, Mona A.; Mahmood, Ali B. (Mesopotamian Journal of Marine Sciences, 2020)
Water erosion is one of the most important environmental problems that cause soil degradation in the areas of water basins in the Syrian coast. The present study aims at determining the spatial distribution of the risk of water erosion of the lands of Al-Hawiz Basin (Jableh region) using the CORINE model. The CORINE model is based on calculating all factors that affect water erosion: soil erosion factor, erosion factor, inclination factor, ground cover fac tor. The soil susceptibility factor for erosion was calculated by estimating both the soil texture, soil depth and gravity percentage for preparing a potential risk map. The feasibility of both the soil susceptibility factor map and the slope map prepared from the use of DEM and the value of the erosion factor were calculated using system technology Geographical information. Then the ground cover map was prepared and classified into two rows according to the degree of protection. The actual risk map was prepared from the seriousness of the potential danger map and the land cover map. The study showed that 12.79% of the studied area is under the control of severe erosion while 32.10% of which had an average risk of erosion, and the risk of erosion was low in the largest part of the area (55.11%). The areas of severe erosion have been concentrated in the central western region of Lake Al-Sadd. It has been shown that vegetation is the most influencing factor in erosion, as it worked to reduce the high risk of possible soil erosion by 50.83%.